Carbamazepine attenuates inducible nitric oxide synthase expression through Akt inhibition in activated microglial cells. (November 2014) - Wang, Chen-Hsu; Hsiao, Che-Jen; Lin, Yi-Nung; Wu, Joe-Wei; Kuo, Yu-Cheng; Lee, Ching-Kuo; Hsiao, George
Abstract Background: Carbamazepine, which was developed primarily for the treatment of epilepsy, is now also useful for the treatment of non-epileptic disorders and inflammatory hyperalgesia. However, the mechanism of its anti-neuroinflammatory action remains poorly understood. Objective: This study elucidates the anti-neuroinflammatory capacity of carbamazepine on microglial activation and the relative mechanisms involved. Materials and methods: The microglial BV-2 cells were pretreated with carbamazepine for 15 min before activation by lipopolysaccharide (LPS). After LPS stimulation, the expression of inducible nitric oxide synthase (iNOS) was analyzed by Western blotting (WB) and reverse transcription-polymerase chain reaction. Signaling proteins and cyclooxygenase (COX)-2 were also evaluated by WB. The levels of nitrate and tumor necrosis factor (TNF)-α were analyzed by the Griess method and enzyme-linked immunosorbant assay, respectively. The formation of intracellular reactive oxygen species (ROS) was examined by fluorescent analysis. Results: Carbamazepine strongly attenuated LPS-induced production of NO and iNOS protein at concentrations of 5, 10, and 20 μM. Consistently, it could markedly suppress iNOS mRNA expression stimulated by LPS. Among the signaling pathways, LPS-mediated IκBα degradation or JNK MAPK phosphorylation was not affected by carbamazepine. Interestingly, it was found that carbamazepine could concentration-dependently inhibit LPS-activated phospho-Akt expression. Nevertheless, LPS-induced ROS production was not affected by carbamazepine. Carbamazepine (20 μM) affected either COX-2 expression or TNF-α production induced by LPS with approximately 70% and 51% inhibition, respectively. Discussion and conclusion: Our findings showed that carbamazepine exerted selective inhibition on LPS-induced microglial iNOS expression through the down-regulation of Akt activation, and thus may play a pivotal role of anti-neuroinflammation in its therapeutic efficacy.